Influence of application time of 32-P labelled triple superphosphate on the fertilizer use efficiency and productivity of potato - Ortiz, Oscar Gonzalo Bastidas; Caballero, Segundo Urquiaga; Alvarez, Adolfo Leon (Pesquisa Agropecuaria Brasileira, 2014)
A study was performed on a soil derived from volcanic ash (Andic Humitropept), in Pasto (Nariño), Colombia, to investigate the influence of additions of 100 and 200 kg P2O 5ha-1, at two application times (planting and 30 days after emergence - DAE), on the fertilizer use efficiency and productivity of potato (Solanum tuberosum L.) cv. Pardo Pastusa. At planting the phosphorus was applied in a continuous row in the furrow, and at 30 DAE at one side of the plant row, and immediately covered with soil from both sides of the furrow. The fertilizer used was 32-P labelled triple superphosphate (143.59 µCi.gP-1). It was found that: a) the phosphorus fertilization significantly increased (P <0.05) the yield (from 19.9 to 37.7 t.ha-1) and the accumulation of P (from eight to 17.8 kg P ha-1) by the tubers, but there was no significant effects of times of the fertilizer application; b) the accumulation of P by the plant accompanied the accumulation of plant dry matter; c) at 75 DAE the fraction of fertilizer P in the plant shoot in the treatment fertilizer at 30 DAE (52.1%) was significantly higher than that fertilized at planting (21.8%), and this corresponded to a P fertilizer use efficiency of 2.4 and 0.82%, respectively.